Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.